Leveraging Academic Social Media to Improve Librarian Research Output in Scopus/Web of Science Indexed Outlets - Adebowale Adetayo; Mufutau Asiru; Olateju Abayomi Adeleke; Augustine I. Enamudu (Journal of Digital Learning and Education, 2023)
The present study aimed to investigate the impact of academic social media utilization on the volume of research output by librarians working in the southwestern region of Nigeria. This investigation adopted a descriptive survey research design and a sample of 363 librarians employed in university libraries located in the southwestern region of Nigeria. Descriptive and inferential statistical methods were utilized to analyze the data collected. The results of the study revealed a low level of research output by librarians in Scopus and Web of Science indexed publications. However, the study also demonstrated that librarians who utilized academic social media platforms such as Figshare, Orcid, and ResearchGate had a higher likelihood of having their research published in outlets indexed in Scopus and Web of Science. In conclusion, this study supports the argument that the utilization of academic social media can enhance the likelihood of publication in Scopus and Web of Science indexed outlets. Based on these findings, it is recommended that efforts be made to increase the utilization of academic social media platforms such as Orcid and ResearchGate among librarians in southwestern Nigeria.